Análise da via de sinalização WNT no câncer gástrico pela imunoexpressão das proteínas E-caderina, betacatenina, APC, TCF-4 e survivina - Lins, Rodrigo Rego [UNIFESP] (2016)
Objective: To determine the expression of E-cadherin, betacatenin, APC, TCF-4 and survivin proteins in gastric adenocarcinoma tissues, to correlate this expression with clinicopathological parameters and to verify the possible participation of the Wnt signaling pathway in gastric carcinogenesis. Method: Clinical and anatomopathological data were collected from the medical records of 71 patients with gastric adenocarcinoma submitted to gastrectomy without neoadjuvant treatment. The material obtained in the surgery was submitted to immunohistochemical analysis to evaluate the expression of E-cadherin proteins (membrane and cytoplasm), betacatenin (membrane, cytoplasm and nucleus), APC, TCF-4 and survivin (cytoplasm and nucleus). The expression rate of each protein was analyzed according to its location in the cell and related to patient clinical and pathological variables of the tumor. Results: The expression rates of the proteins were as follows: E-cadherin (3% in the membrane, 63.6% in the cytoplasm), betacatenin (29.7% in the membrane, 23.4% in the cytoplasm, 3,1% in the nucleus), APC (94.9% in the cytoplasm, 89.8% in the nucleus), TCF-4 (25.4% in the cytoplasm, 19.4% in the nucleus) and survivin (93.9% in both cytoplasm and nucleus). There was a relationship between the expression of E-cadherin in the cytoplasm with female patients (p = 0.014), membrane betacatenin with female patients (p = 0.024), betacatenin in the cytoplasm with tumors <5cm in diameter (p = 0.041 ), APC in the cytoplasm with proximal tumors (p = 0.047), TCF-4 in the nucleus with diffuse type of Lauren classification (p = 0.017) and pT4 tumors (p = 0.002) and survivin both nucleus and cytoplasm with Lauren's intestinal tumors (p = 0.05). Conclusion: The Wnt/betacatenin is not involved in gastric carcinogenesis. However, the high frequency of survivin allows us to suggest that other signaling pathways must be involved in the transformation of gastric tissue. Positive TCF-4 immunoexpression in the cell nucleus is related to T4 gastric carcinomas and Lauren?s diffuse tumors. Positive immunoexpression of survivin in the nucleus of gastric carcinoma cells is related to Lauren?s intestinal tumors.